Gestao da informaçao e do conhecimento e teoria da complexidade no contexto empresarial : um estudo no setor de comunicaçao e tecnologia - Pinheiro dos Santos, Beatriz Rosa (Palabra Clave.)
A society immersed in large amounts of information must be guided by the integration of the most varied organizational and informational contexts, in order to produce knowledge with inter, multi, multi and transdisciplinary characteristics. Thus, the following research problem is presented: Does the company contemplated by the research, belonging to the field of communication and technology, have an organizational culture focused on the promotion and development of information and knowledge management based on complex thinking? The objective of the research is to verify if this company presents factors that indicate an organizational culture focused on the promotion and development of information and knowledge management in its work practices, based on complexity theory. For this, a descriptive-exploratory research of a qualitative nature was carried out, using as a research tool the interview script, and as a method of analysis, the 'Content Analysis'. The results show that the organizational environment develops more strongly the practices of information management than of management of knowledge, based on some principles of complex thinking developed in parallel with the information management, and it can be pointed out that of the seven principles of complex thinking, those developed in the researched enterprise are: hologramatic principle, self-eco-organization principle, retroactive circle principle and recursive circle principle